2022
DOI: 10.1039/d2cy00303a
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst sites and active species in the early stages of MTO conversion over cobalt AlPO-18 followed by IR spectroscopy

Abstract: Reaction-time resolved IR spectroscopy highlights the role of CO and surface –OCH3 in the MTO conversion catalysed by CoAPO-18 with maximised concentration of acidic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…110 While the exact mechanism to produce the first olefin still needs to be resolved, the latest work by the Bordiga group observed the presence of free vibrating CO throughout the MTO reaction catalyzed by MAPO-18s and suggested that CO may play a role beyond the first C−C bond initiation. 111 Zeolite-catalyzed carbonylation mechanisms are described in more detail in Sections 4.1 and 4.2. For a more extensive review of hydrocarbon pool initiation mechanisms, we refer the reader to the recent review by Yarulina et al 42 Besides CO, water is another molecule of interest in the MTH process, which is relevant for the integrated process from CO x to hydrocarbons.…”
Section: Methanol-mediated Co X Conversion To Hydrocarbons 21 a Short...mentioning
confidence: 99%
See 1 more Smart Citation
“…110 While the exact mechanism to produce the first olefin still needs to be resolved, the latest work by the Bordiga group observed the presence of free vibrating CO throughout the MTO reaction catalyzed by MAPO-18s and suggested that CO may play a role beyond the first C−C bond initiation. 111 Zeolite-catalyzed carbonylation mechanisms are described in more detail in Sections 4.1 and 4.2. For a more extensive review of hydrocarbon pool initiation mechanisms, we refer the reader to the recent review by Yarulina et al 42 Besides CO, water is another molecule of interest in the MTH process, which is relevant for the integrated process from CO x to hydrocarbons.…”
Section: Methanol-mediated Co X Conversion To Hydrocarbons 21 a Short...mentioning
confidence: 99%
“…A hint in favor of Path (b), in which multiple “first C–C bonds” may be formed from a single CO molecule, arises from prior studies in which the coke formed in the MTH initiation zone of a ZSM-23 catalyst contained close to 2 orders of magnitude more C than the CH 4 formed in the same zone . While the exact mechanism to produce the first olefin still needs to be resolved, the latest work by the Bordiga group observed the presence of free vibrating CO throughout the MTO reaction catalyzed by MAPO-18s and suggested that CO may play a role beyond the first C–C bond initiation . Zeolite-catalyzed carbonylation mechanisms are described in more detail in Sections and .…”
Section: Methanol-mediated Cox Conversion To Hydrocarbonsmentioning
confidence: 99%
“…The MTH process enables replacement of conventional fossil fuels such as coal, crude oil and natural gas with carbon neutral renewable methanol feedstock to produce gasoline, olefins and aromatics, and therefore can play a key role in achieving the net zero carbon emissions target by 2050 [5]. Consequently, there is a growing interest in unravelling the fundamental reaction and deactivation mechanisms [4,[6][7][8][9][10][11]. A consensus on the role of Brønsted acidity in the first C-C bond formation mechanism from C1 methanol molecule has emerged [4,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a growing interest in unravelling the fundamental reaction and deactivation mechanisms [4,[6][7][8][9][10][11]. A consensus on the role of Brønsted acidity in the first C-C bond formation mechanism from C1 methanol molecule has emerged [4,[6][7][8][9][10]. However, studies on the initial stage of the MTH process involving adsorption, diffusion and reaction of molecules at the Brønsted acid site are very limited [12][13][14][15][16]; and as diffusion rates often determine the reaction rates, the understanding of diffusion dynamics is crucial for designing and tailoring further the acidity and porous architecture for the development of an efficient catalytic process [17].…”
Section: Introductionmentioning
confidence: 99%
“…82,91,92 A second hydride transfer yields dimethoxymethane or CO and again H 2 or CH 4 as byproducts. [93][94][95] In the CO-pathway, CO can be methylated to surface acetate [96][97][98] and ketene, 99 which is identical to carbonylation of methanol or DME. [100][101][102][103][104][105] These are important intermediates during the MTO initiation.…”
Section: Introductionmentioning
confidence: 99%